A GIS-Based Study on Spatial Pattern, Accessibility and Equity of Urban Cultural Resources: A Case Study of Red Culture Resources in Shanghai - Shu-Qing Chen; Jian Zhang; Wen-Lei Luan; Xi Luo (Buildings, 2025)
Culture represents the core and ultimate value of a city, serving as a foundation for its economic and social development. However, with rapid urban expansion and increasing globalization, issues related to the spatial distribution pattern, accessibility and equity of cultural resources have become more prominent. This study proposes an integrated GIS-based framework combining ANN, Kernel Density, accessibility, and LQ analyses. It evaluates cultural service coverage across walking, cycling, and driving modes under varying travel durations (5–30 min). Both area-based accessibility and residential-based accessibility are considered. Additionally, the study incorporates Location Quotient (LQ) Analysis for low-income communities across these travel modes and accessibility types to assess spatial equity. The framework is validated through a case study of red cultural resources in Shanghai (China). The results show significant mismatches between area accessibility and residential accessibility in certain administrative districts, particularly highlighting disparities in cultural service provision for disadvantaged populations. These findings suggest incorporating residential-oriented accessibility and equity-based metrics into planning practices. This method supports more accurate and equitable allocation of cultural resources and informs evidence-based decisions in facility planning, urban function optimization, and spatial management.